Kissing nevus of the penis: a case report and dermatoscopic findings - Nivea Godinho; Gisele Alborghetti Nai; Arnaldo Luiz Flávio Schaefer; Luiza Vasconcelos Schaefer (Sociedade Brasileira de Dermatologia, 2017)
Abstract Divided nevus, also known as kissing nevus, is a rare variant of congenital melanocytic nevi in which there are two adjacent nevi in areas of the body that undergo embryonic cleavage. The original description of this type of lesion was on the eyelid. The location on the penis is even rarer, with only 17 case reports in the literature so far, and only one of them described the dermoscopic findings. We report the case of a patient with divided nevus of the penis and its clinical, dermoscopic and histopathological features.